The Brain Work Process: A Multidisciplinary Analysis of Neuroplasticity, Cognition, and Human Thought - Refinal; Ismaiza Busti; Ahmad Lahmi; Dasrizal Dahlan; Rosniati Hakim; Abdulrohim E-sor (Walidem Institute and Publishing, 2025)
Objective: This study aims to provide a comprehensive understanding of how the human brain functions in cognitive processes such as thinking, reasoning, and decision-making. Theoretical framework: The research is grounded in a theoretical framework that integrates neuroscience and cognitive psychology, focusing on brain structure, neural networks, and the dynamics of neuroplasticity. Literature review: The literature review explores the interconnectivity between various parts of the brain, such as the cerebrum, cerebellum, brainstem, hippocampus, and amygdala, and their roles in memory, emotion, perception, and high-order cognitive tasks. Methods: Employing a qualitative method through library research, this study synthesizes data from academic books, journal articles, dissertations, and digital resources. A descriptive-analytical approach was used to organize and interpret findings across themes, including memory processing, brain development, thinking stages, and influencing factors such as emotion, nutrition, and environmental conditions. Results: The findings reveal that brain function and cognitive thinking are deeply interconnected. The brain processes information through electrical and chemical signals, stores it in short- or long-term memory, and enables the execution of thought processes through structured phases: perception, attention, understanding, reasoning, decision-making, and evaluation. Neuroplasticity plays a critical role in allowing the brain to adapt and learn continuously throughout life. Implications: The study implies that optimizing brain health directly enhances thinking capabilities, which is essential for personal growth, learning, adaptability, and innovation. Practical implications span across education, healthcare, and mental performance strategies. This research contributes to bridging the scientific gap between biological brain function and human thought processes, offering valuable insights for designing brain-friendly environments, promoting lifelong learning, and fostering mental well-being in the digital age. Novelty: The novelty of this study lies in its multidisciplinary integration of neuroanatomy, behavioral science, and cognitive analysis, presented in a holistic and applicable manner.